Genetic Engineering for Tolerance to Fusarium Wilt in Musa Sapientum Cv Rastali (AAB) - Subramaniam, Sreeramanan (2005)
This study aims at developing tolerant Pisang Rastali (AAB) to Fusarium wilt via genetic engineering. Several considerations support that banana is a good candidate crop that could benefit from biotechnology applications.